2014
DOI: 10.1097/bor.0000000000000089
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis, diagnosis and treatment of lupus nephritis

Abstract: Purpose of review Renal involvement is a major cause of morbidity and mortality in systemic lupus erythematosus (SLE). In this review we provide an update on recent discoveries in the pathogenesis, diagnosis, and treatment of lupus nephritis (LN). Recent findings Localized long-lived plasma cells have been identified as playing an important role in LN. In addition, the roles of aberrant expression of microRNAs and pro-inflammatory cytokines have been explored. Early diagnosis is important for effective treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 78 publications
(82 reference statements)
1
92
0
5
Order By: Relevance
“…Relevant immunological markers were encountered in the majority of cases, with nearly 98% positive for antinuclear antibodies. Previous studies revealed that those who present at a younger age with severe nephritis and nervous system affections have poorer prognosis (2,27).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant immunological markers were encountered in the majority of cases, with nearly 98% positive for antinuclear antibodies. Previous studies revealed that those who present at a younger age with severe nephritis and nervous system affections have poorer prognosis (2,27).…”
Section: Discussionmentioning
confidence: 99%
“…Lupus nephritis is a major cause of morbidity and mortality in lupus patients, but diagnosis and monitoring remains challenging. Further, despite aggressive immunosuppressive therapy that is often complicated by serious adverse events, the incidence of end-stage kidney disease from lupus nephritis has not declined [7,8]. This emphasizes the need for a better understanding of the pathogenesis of lupus nephritis and the development of novel biomarkers to predict and monitor renal involvement in lupus patients.…”
Section: Introductionmentioning
confidence: 99%
“…Immune cells, cytokines, and epigenetic factors have all been recently implicated in LN pathogenesis (Schwartz et al, 2014). Primary IgAN chemical investigations have revealed that IgA1 molecules from patients differ in their glycosylation pattern compared with IgA1 from healthy subjects.…”
Section: Discussionmentioning
confidence: 99%